RISK MANAGEMENT PROCESS OF "EV-STATION ELECTRIC VEHICLE CHARGING STATION" IN INDONESIA - I Putu Dhitya Punarbhawa; Rhian Indradewa (Jurnal Scientia, 2023)
The growth of motor vehicles in Indonesia is increasing every year. The development of EVs from 2011 to 2019 increased significantly. In 2015 the total EV was 102 units and in 2019 it reached 520 units. The acceleration of vehicle conversion from Internal Combustion Engine (ICE) to Battery Electric Vehicle (BEV) requires supporting infrastructure, one of which is the availability of SPLU (Public Electric Charging Station) and SPKLU (General Electric Vehicle Charging Station). SPLU has a power of 5.5 kVA to 22 kVA. Companies can make smarter decisions for future business development. eV-Station, for example, has integrated ISO 31000:2018 as a cornerstone in carrying out the company's risk management process and adopted a clearly visible framework. As a result of this process, we identified nine high-risk categories that require special attention to mitigation activities. The risk management team will continuously monitor and evaluate the mitigation process for sustainable outcomes.